Informing the TB suspect for sputum sample collection and communicating laboratory results in Nicaragua: a neglected process in tuberculosis case finding La información al caso sospechoso de TB para la recolección de la muestra de esputo y la comunicación de resultados de laboratorio en Nicaragua: un proceso descuidado en la pesquisa de casos de tuberculosis - Jean Macq; Alejandro Solis; Harry Velázquez; Bruno Dujardin (Instituto Nacional de Salud Pública, 2005)
OBJETIVO: valorar el proceso de información del paciente antes de la producción de esputo, la calidad de la muestra de esputo, y la transmisión de los resultados del examen microscópico del esputo a los sospechosos de tuberculosis (TB) en tres áreas de Nicaragua. MATERIAL Y MÉTODOS: (a) entrevistas dirigidas a sospechosos de TB cuya expectoración ha sido examinada para BK; (b) entrevistas dirigidas al personal de salud de tres áreas de estudio (c) la evaluación de la calidad de la expectoración. RESULTADOS: Un total de 115 sospechosos de TB y 33 trabajadores de la salud fueron entrevistados; 625 muestras de esputo fueron examinadas. Los resultados muestran varias debilidades en el proceso de información a los sospechosos antes de la producción de esputo. CONCLUSIÓN: Este estudio revela un aspecto del proceso de diagnóstico de la TB demasiado ignorado. Los resultados ilustran la importancia de evaluar de forma rutinaria el proceso completo de diagnóstico de la TB. Informing the TB suspect for sputum sample collection and communicating laboratory results in Nicaragua: a neglected process in tuberculosis case finding OBJECTIVE: To assess the patient information process before sputum sample collection, the quality of sputum sample and transmission of acid-fast bacilli (AFB) examination results to TB suspects, in three local areas of Nicaragua. METHODS: (a) directed interviews of consecutive series of TB suspects whose sputum had been examined for AFB; (b) directed interview of health personnel; and (c) assessment of the sputum sample quality. RESULTS: A total of 115 TB suspects and 33 health personnel were interviewed and 625 sputum samples were assessed. Results show multiple weaknesses in the process of information to the patient during sputum collections, as well as in the communication of results. CONCLUSIONS: This study unveiled an aspect usually overlooked of case finding, that is, the information process during sputum production, sputum sample quality, and the communication of results to the TB suspects. The results illustrate the need for routine assessment of the whole diagnostic process.